AtHB23 participates in the gene regulatory network controlling root branching and reveals differences between secondary and tertiary roots - Perotti, María Florencia (2019)
In Arabidopsis, lateral root (LR) development is mainly controlled by several known auxin-regulated transcription factors (TFs). Here, we show that AtHB23 (a homeodomain-leucine zipper I TF) participates in this intricate network. Our study of the expression pattern of AtHB23 revealed that it is transcriptionally activated in the early stages of secondary LR primordium (LRP). We found that AtHB23 directly limits the expression of LBD16, a key factor in LR initiation, and also directly induces the auxin transporter gene LAX3.We propose that this HD-Zip I mediates the regulation of LAX3 by ARF7/19. Furthermore, AtHB23 plays distinct roles during the formation of secondary and tertiary roots, exhibiting differential expression patterns. ATHB23 is expressed throughout the tertiary root primordium, whereas it is restricted to early stages in secondary primordia, likely later repressing LBD16 in tertiary LR development and further inhibiting root emergence.Our results suggest that different genetic programs govern the formation of LRP from the main or secondary roots, thereby shaping the global dynamic architecture of the root system.